Peran Manajemen Pendidikan Islam dalam Pengembangan Lembaga Pendidikan dan Masyarakat - Rifatul Uliah; Try Susanti; Wita Seftiani; Aina Mardlaatillah; Wahyu Kurniawan (STKIP Subang, 2025)
This study aims to analyze the concepts, roles, and implementation strategies of Islamic Education Management (IEM) in the development of Islamic educational institutions and society. The research employed a library research method by collecting data from books, scholarly journals, and relevant documents. The data were analyzed qualitatively through classification, interpretation, and synthesis. The findings indicate that IEM is an educational management process grounded in Islamic values, encompassing the functions of planning, organizing, implementing, and supervising. These functions are integrated with the principles of honesty, trustworthiness, justice, and responsibility as managerial foundations. In the context of developing Islamic educational institutions, IEM plays a strategic role in curriculum management, improving human resource quality, developing facilities and infrastructure, managing funding, as well as optimizing public relations and special services. All these aspects are directed toward achieving continuous institutional quality improvement. Moreover, IEM contributes significantly to community development through character building, strengthening tolerance values, and developing human resources who are ethical, productive, and adaptive to socio-cultural changes. This study affirms that professional implementation of IEM, grounded in Islamic values, serves as a driving force in enhancing the quality of education and fostering holistic community development.